Teaching English to Young Learners through Games and Songs - Damayanti, Sri; Faozah, Siti (ENGLISH JOURNAL, 2016)
Young English language learners have different characteristics compared to those adult English language learners. This would of course result in consideration on the teachers’ side, particularly, about how to effectively and appropriately teach them inside the classroom. The treatment given by the EYL teachers to their students are supposed to be different. Young language learners always prefer to have the learning sessions in interesting and challenging ways. These are believed to be able to be achieved through implementing games and songs. This paper tries to elaborate how games and songs can be used in helping EYL teachers create positive atmosphere in the classroom so that the learning process can be much more interesting and meaningful.